PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN PADA ASYIFA SWALAYAN SAMARINDA - Alita Khoiriati (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
Experiential marketing is a concept to create a positive customer experience in using a company's products or services. Asyifa Swalayan is a company engaged in the retail business, therefore the experiential marketing strategy is very influential for Asyifa Swalayan to attract customers to make repeat purchases. This study aims to test and analyze the effect of Experiential Marketing (X) on Customer Loyalty (Y) on Asyifa Swalayan customers. This type of research approach used is quantitative research. The population in this study amounted to 96 customers. The sampling method used was purposive sampling technique where the technique had criteria in accordance with the conditions specified as a sample. The data collection technique was carried out by means of observation, interviews and questionnaires. Meanwhile, the data analysis technique used simple linear regression analysis method and used SPSS version 23. The results showed that the variable Experiential Marketing had a significant effect on Customer Loyalty at Asyifa Swalayan Samarinda. This can be seen from the simple linear regression value of 0.402. With the value of the correlation coefficient (R) 0.68 4 means that there is a strong positive relationship between the variables Experiential Marketing on customer loyalty, and the value of determination (R2) 47%, which means that the variable Experiential Marketing on customer loyalty, while 53% are influenced by variables others who were not examined in this study. Suggestions to Asyifa Swalayan, companies should provide facilities in the form of children's toys so that customers focus on shopping and prevent other negative things such as breaking, scattering, and destroying items in the store.